SUFISTIC LANGUAGE STYLE IN AL-QUSHAYRI’S NAHW AL-QULUB - Huda, Rizki Fathul; Buana, Cahya (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2021)
This study aims to reveal the forms of language style used in "Nahw al-Qulub al-Kabir," the work of al-Qushayri with aesthetic values. It also intends to reveal the meaning effects implied in the language forms. This study uses a stylistic approach in analyzing text's language style, especially at the construction of the morphological level, syntax, and imagery. This research shows that the language style constructs the morphological level through word selection, word forms, and movement from one-word form to another. At the syntactic level, there are unusual sentence patterns and high intensity of using ma mausul as khobar. At the imagery level, al-Qushyari uses many patterns of isti'arah, tashbih, kinayah, saja', iqtibas, and tauriyyah. The extraction of meaning effect also carries a solid sufistic teachings dimension, including takhalli, tahalli, tajalli, ma’rifat, maqam jama’ and farq, and the teachings of Akhlaqi Sufism.